APLIKASI KARAKTERISTIK ARSITEKTUR FUTURISTIK PADA TERMINAL PENUMPANG PELABUHAN YOS SUDARSO DI KOTA AMBON - Ekine Wahyuning Tyas; Agung Kumoro Wahyu; Widi Widi Suroto (Universitas Sebelas Maret Surakarta, 2017)
Maluku as one of the archipelago provinces in Indonesia would require a sea transportation system to improve movement of goods and services inter-islands both within and outside of the Province. Ambon City as the capital of Maluku Province has an important role in accommodating it . Ambon City itself currently has six ports with different functions. One of the main ports is the Port of Yos Sudarso Ambon which currently accommodates two functions. First, as a port of passenger and second as a container port. However, along with the increasing container demand and inadequate port area. Then, there are various proposals which proclaimed in various regional and national development programs to focus on the transition function of Yos Sudarso Port in accommodating the activities of departure and arrival of passengers and eliminate the function of containers activity. The futuristic architectural approach is intended to find the need for architectural masterpieces of modern character and stand out along the Ambon Waterfront City development area. This approach represents progress, something new that is different from the other building on the environment and speed points which is identical with building of transportation. So it is expected that through this approach can be generated a redesign concept that can provide first impression for its users.Keyword : Port, Passanger Terminal, Futuristic Architecture, Transportation Building